2006
DOI: 10.1177/0192513x06287249
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Resource Receipt of New Mothers

Abstract: U.S. federal policies do not provide a universal social safety net of economic support for women during pregnancy or the immediate postpartum period but assume that employment and/or marriage will protect families from poverty. Yet even mothers with considerable human and marital capital may experience disruptions in employment, earnings, and family socioeconomic status postbirth. We use the National Survey of Families and Households to examine the economic resources that mothers with children ages 2 and young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
1
19
2
Order By: Relevance
“…Household composition is one indicator of social integration. The presence of other adult household members—such as a partner, parent, or other relative—may provide financial, instrumental, or emotional resources, enhancing a mother’s sense of support (Harknett, 2006; Nichols, Elman, & Feltey, 2006; Park, 2005). In a recent study, Harknett and Hartnett (2011) found that marriage and cohabitation were associated with higher rates of perceived support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Household composition is one indicator of social integration. The presence of other adult household members—such as a partner, parent, or other relative—may provide financial, instrumental, or emotional resources, enhancing a mother’s sense of support (Harknett, 2006; Nichols, Elman, & Feltey, 2006; Park, 2005). In a recent study, Harknett and Hartnett (2011) found that marriage and cohabitation were associated with higher rates of perceived support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asians, African Americans and Latinas), new mothers in poverty were more likely to share co-residence and receive public assistance. However, new mothers above the poverty level were more likely to receive monetary assistance from family and friends (Nichols et al 2006). A notable difference between white and non-white mothers is that white mothers were less likely to reside with kin (Hogan et al 1990), suggesting a possible difference in cultural expression of family structure or social class (Sarkisian et al 2007).…”
Section: Other Factors That Impact Kin Supportmentioning
confidence: 99%
“…Family in community-type network Extended family Focal family Overall, grandparents living in close proximity reduced the risk of poverty, but giving monetary assistance was actually linked to increased risk of poverty (Nichols et al 2006). Access to support also appears linked to age as young mothers in their mid-20s receive significantly less support than younger mothers (Parish et al 1991;Lawton et al 1994).…”
Section: Clan Membersmentioning
confidence: 99%
“…Changes in marital, family and household status have significant impacts on welfare participation (Cheng and McElderry, 2007;Mulia and Schmidt, 2003), although one study found that the number of persons in new mothers' social networks did not significantly affect the mothers' AFDC receipt (Nichols et al, 2006). Changes in marital, family and household status have significant impacts on welfare participation (Cheng and McElderry, 2007;Mulia and Schmidt, 2003), although one study found that the number of persons in new mothers' social networks did not significantly affect the mothers' AFDC receipt (Nichols et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%